Mothers' Education and Girls' Achievement in Kibera: The Link With Self-Efficacy. (March 2018) - Abuya, Benta A.; Mumah, Joyce; Austrian, Karen; Mutisya, Maurice; Kabiru, Caroline
Research evidence has established the importance of mothers' education and their children's educational achievement. However, little has been done to establish the association between mothers' education with girls' literacy and numeracy scores, while linking it with self-efficacy. Using baseline data collected in Kibera informal settlement in 2015 as part of the Adolescent Girls Initiative–Kenya (AGI-K), this article tests the mother–child education achievement hypothesis while taking into account girls' self-efficacy. Results show a significant association between parental education and numeracy and cognitive scores at the bivariate level. In addition, interaction effects of mother's and father's education showed that girls whose mothers had at least some secondary education significantly performed better in numeracy, while the performance increased even more with increased father's level of education. Findings also show that on average, girls' numeracy and cognitive scores significantly increased by half of a standard deviation for a unit increment in self-efficacy. One policy implication is that investments into the secondary education of mothers in support of their daughter's education need to strengthen individual attributes of girls in self-efficacy.